Influência da adição de microcelulose cristalina nas propriedades do estado fresco de argamassas de revestimento - Jesus, Sidnei Marcondes de (2023)
Understanding the effects of crystalline microcellulose in coating mortars is essential for designing more durable, stronger, and efficient materials in construction. Therefore, the present work aims to verify the influence of adding levels of 0.2%, 0.4% and 0.6% of crystalline microcellulose (MCC) on the fresh properties of coating mortars. The study was developed considering the impact of microcellulose additions on coating mortars through consistency, through the flow-table test, mass density, incorporated air content and rheological behavior through the squeeze-flow test. Based on the results obtained, it was possible to conclude that the incorporation of crystalline microcellulose resulted in a decrease in the consistency of the mortars. Concentrations of 0.2% and 0.4% provided an increase in air incorporation, plasticity in fifteen minutes of the mixture and a reduction in mass density, indicating that these percentages can act to improve the application process, facilitating the execution of coating mortars. However, it was possible to observe a change in the rheological behavior, after thirty minutes of mixing, where the mortars with the addition of crystalline microcellulose reduced the displacements in relation to the reference, indicating that the high water retention capacity of microcellulose can influence the plasticity of the mortars over the mixing time.